The Training on Making Game-Based Learning Media with Quizizz Application for Teachers at SDN Banjaragung 1 Mojokerto - Wiyanto, Muhammad Saibani; Tony Hendrawan, Kahan (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
Abstract: The problem faced by teachers in teaching is still using less interesting learning media, such as sending documents, photos or videos containing learning material. This learning media makes students quickly bored. Moreover, students who are still at elementary school level are more interested in things that are game-based or that require students to participate in the process of understanding the material. One solution is to learn while playing or providing material using methods that are very popular with students at the elementary level. According to the results of observations about the problems that occurred at SD Negeri Banjaragung 1 Mojokerto, the researcher took an idea to conduct training in making game-based learning media. The Quizizz Application Helps All Teachers at Banjaragung 1 Mojokerto Elementary School. This is provided to provide guidance and training to teachers at SD Negeri Banjaragung 1 Mojokerto on how to create interesting and game-based learning media with the help of the Quiziiz application which can be operated via laptop or mobile phone. The result of this training activity is that teachers can create fun learning media through the Quizziz application well. Of the 13 participants who took part in this activity, all of them were able to apply the material presented by the service team in using the quizizz application.